ANALISIS PENGARUH LEVERAGE, SET KESEMPATAN INVESTASI, KEPEMILIKAN MANAJERIAL, DAN CORPORATE GOVERNANCE TERHADAP KEBIJAKAN DIVIDEN - Tina Rosaline; Megawati Oktorina (Universitas Ahmad Dahlan, 2014)
Dividend policy is one of the important company policy, because it can be a signal for investors to see the value of the company. The dividend policy in each company has different characteristics from one another. This study aimed to examine the effect of leverage, the investment opportunity set, managerial ownership, and corporate governance on dividend policy. The sample in this study were 115 company year listed in the Indonesia Stock Exchange and distribute dividends during the period 2010 to 2012. This study used multiple linear regression to analyze the data and test the hypothesis. The results showed that the dividend policy is influenced by the investment opportunity set measured by a price-earnings ratio and the market value of equity to book assets. Meanwhile, financial leverage, managerial ownership, corporate governance, and firm size as control variables did not significantly affect dividend policy.